Development of RP-HPLC Method for Simultaneous Determination of Bilastine and Montelukast by Qbd Approach and Its Validation: Pharmaceutical Science-Pharmaceutical Analysis - Ahmed, Aejaz; Mehfuza U, Manjra; Mubina, Lajporiya; Nazifa, Sayyed; Seema, Patel; Khan, G.J.; Majaz Ahamad, Qazi (International Journal of Life Science and Pharma Research, 2023)
This study proposes to develop and validate the RP-HPLC method for Bilastine (BIL) and Montelukast (MKT) byQbD to substantiate the RP-HPLC analysis as per ICH validation guidelines. Quality by Design (QbD) allows the accomplishmentof specific unsurprising quality with a predetermined and wanted determination. The simultaneous estimation of BIL and MKTwas performed with C18 (4.6×250 mm, 5-μm particle size) with an LC-10AD pump and PDA detector. The mobile phaseemployed methanol and ammonium acetate buffer pH-3.6 at 85:15 v/v. The flow rate was maintained at 1.0 ml/min, and BIL andMKT were detected at 249nm and 293 nm by UV detector, respectively. The HPLC method provided linear responses found inthe 200–600 μg/ml range. The correlation coefficient was 0.9995 for BIL and 0.9991 for MKT. The LOD and LOQ for BIL andMKT were found to be 0.493, 1.495 μg/ml, and 0.693, 2.100, respectively. The percentage recovery for BIL was 95.33 to 102.06,and for MKT was 96.31 to 104.05, respectively. Calculated information acquired for both the preliminaries roughly coordinateswith the information given by Design expert programming, showing the chromatographic condition’s genuineness. Design-Expertversion 10 ("DX10") software has calculated this calculation, setting a composite design of significant parameters. A newselective, rapid, accurate, precise, and sensitive RP-HPLC method was developed and evaluated for the simultaneousdetermination of Bilastine (BIL) and Montelukast sodium (MKT) in a bulk and pharmaceutical dosage form. This method is usefulin the routine quality analysis of combinations of BIL and MKT in bulk and its tablet formulations.